Insulin resistance alters hepatic ethanol metabolism: studies in mice and children with non-alcoholic fatty liver disease. Issue 9 (25th May 2015) - Engstler, Anna Janina; Aumiller, Tobias; Degen, Christian; Dürr, Marion; Weiss, Eva; Maier, Ina Barbara; Schattenberg, Jörn Markus; Jin, Cheng Jun; Sellmann, Cathrin; Bergheim, Ina
Abstract : Objective: Increased fasting blood ethanol levels, suggested to stem from an increased endogenous ethanol synthesis in the GI tract, are discussed to be critical in the development of non-alcoholic fatty liver disease (NAFLD). The aim of the present study was to further delineate the mechanisms involved in the elevated blood ethanol levels found in patients with NAFLD. Design: In 20 nutritionally and metabolically screened children displaying early signs of NAFLD and 29 controls (aged 5–8 years), ethanol plasma levels were assessed. Ethanol levels along the GI tract, in vena cava and portal vein, intestinal and faecal microbiota, and activity of alcohol dehydrogenase (ADH) and cytochrome P450 2E1 (CYP2E1) were measured in wild-type, ob/ob and anti-TNFα antibody (aT) treated ob/ob mice. Results: Despite not differing in dietary pattern or prevalence of intestinal overgrowth, fasting ethanol levels being positively associated with measures of insulin resistance were significantly higher in children with NAFLD than in controls. Ethanol levels were similar in portal vein and chyme obtained from different parts of the GI tract between groups while ethanol levels in vena cava plasma were significantly higher in ob/ob mice. ADH activity was significantly lower in liver tissue obtained from ob/ob mice in comparison to wild-type controls and ob/ob mice treated with aT. Conclusions: Taken together, our data of animal experiments suggest that increased blood ethanol levels in patients with NAFLD may result from insulin-dependent impairments of ADH activity in liver tissue rather than from an increased endogenous ethanol synthesis. Trial registration number: NCT01306396.